2021
DOI: 10.21203/rs.3.rs-739482/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Expression of lncRNA HEIH is Helpful in the Diagnosis of Non-Small Cell Lung Cancer and Predicts Poor Prognosis

Abstract: Objective: This study aims to investigate the expression and clinical value of long non-coding RNA (lncRNA) HEIH in peripheral blood of patients with non-small cell lung cancer (NSCLC).Methods: Healthy subjects (N=70), patients with lung squamous cell carcinoma (LUSC, N=70) and patients with lung adenocarcinoma (LUAD, N=80) were included. LncRNA HEIH expression in peripheral blood of included subjects was detected. According to the median expression of lncRNA HEIH, LUSC and LUAD patients were divided into lncR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A total of the 35 articles were obtained by ltering from the four databases mentioned above. After completing the elimination of duplicates and irrelevant study topics, the titles, abstracts and full texts of these studies were read further and 11 articles were nally included in our Meta-analysis [16][17][18][19][20][22][23][24][25][26] . All included studies were from China and Contain a total of 1,227 patients with sample sizes of 35 to 215, and published between 2011 and 2022.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of the 35 articles were obtained by ltering from the four databases mentioned above. After completing the elimination of duplicates and irrelevant study topics, the titles, abstracts and full texts of these studies were read further and 11 articles were nally included in our Meta-analysis [16][17][18][19][20][22][23][24][25][26] . All included studies were from China and Contain a total of 1,227 patients with sample sizes of 35 to 215, and published between 2011 and 2022.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…LncRNA High expression in hepatocellular carcinoma (HEIH), also named as hepatocellular carcinoma upregulated EZH2-associated lncRNA, is a newly identi ed lncRNA and was found to be located at human chromosome chr3q13.31 [15] . In recent years, overexpression of HEIH has been uncovered in a wide range of cancer types, e.g., breast cancer [16] , colorectal cancer [17] , esophageal squamous cell carcinoma [18,19] , gastric cancer [20,21] , retinoblastoma [22] , lung squamous cell carcinoma [23] , lung adenocarcinoma [23] , ovarian cancer [24] , hepatocellular carcinoma [25] and melanoma [26] , and it was found that its overexpression has some prognostic value. In breast cancer, HEIH expression levels was positively correlate with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%